Male Addicts’ Experiences on Predictors of Relapse to Drug Use: A Directed Qualitative Content Analysis - Mousali, Amirabbas; Moradveisi, Latif; Barati, Majid; Moeini, Babak; Bashirian, Saeed; Sharma, Manoj; Mohammadi, Younes (Addicta: The Turkish Journal on Addictions, 2020)
Addiction relapse is one of the most essential aspects of addiction. This study aims to explain the male addicts’ experiences on predictors of relapse to drug use based on a multitheory model (MTM). This study was directed qualitative content analysis that was conducted on 17 addicts referred to addiction treatment centers in Hamadan City, Iran, in 2019. The samples were recruited using the purposive sampling method. Semistructured, individualized interviews were used to collect data, and then, data were analyzed using a theory-based content analysis approach. Data analysis led to the extraction of 19 main codes that were categorized in six predetermined themes of MTM constructs consisting of participatory dialog, behavioral confidence, changes in physical environment, emotional transformation, practice for change, and changes in social environment. The main predictors of drug use relapse were emotional transformation, changes in social environment, and changes in physical environment. Findings of this study showed that the unpleasant emotions, peer pressure, and access to drugs were the most critical factors in increasing drug use relapse. Therefore, designing appropriate interventions to prevent relapse of drug use based on the results of this study appears to be useful.
Keywords: Substance use; addiction; recurrence; directed content analysis; multitheory model